Manajemen Resiko di Proyek Konstruksi - Sandyavitri, Ari (Department of Civil Engineering, Diponegoro University, 2009)
Time delay in the project execution phase causes cost escalation. This paper demonstrated the magnitude of severness of time delay affected to an increase of the project cost during the construction of bridge in Indragiri Hulu District. It wa evaluated that the project construction program was planned for 120 days but it was delayed up to 255 days. The time delay of 135 days within the project affected an increase of the constractorâ€™s additional expenses about Rp. 703 million. By simulating various parameters of risks, it was found that; (i) based on the â€œwhat it isâ€ scenario, 80 % probability the project was predicted to delay up to 118 days (cost of Rp 686 million); and (ii) by the implementation of risk management procedure encompassing 6 (six) risk mitigation elements it was estimated that 80% probablility of project delay may reach 46 days (cost Rp 361 million). The reduction of time delay and cost overruns may reach 50%.Â Hence, it demonstrates that the implementation of risk management procedure may control project risks systematically. Key words; risk analysis, time delay, costs, project, probabilityPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3419[How to cite: Sandyavitri, A. (2009). Manajemen Resiko di Proyek Konstruksi, Jurnal Media Komunikasi Teknik Sipil, 17 (1): 23-38]